Effect of veterinary feed directive rule changes on tetracycline-resistant and erythromycin-resistant bacteria (Salmonella, Escherichia, and Campylobacter) in retail meats in the United States. - Shamim Sarkar; Chika Okafor (PLoS ONE, 2023)
Background Antimicrobial-resistant bacteria are a growing public health threat. In 2017 the U.S. Food and Drug Administration implemented Veterinary Feed Directive (VFD) rules changes to limit medically important antimicrobial use in food-producing animals, combating antimicrobial-resistant bacteria. The effect of the VFD rule changes on the occurrence of bacteria resistant to medically-important antimicrobials in retail meats is yet to be investigated in the U.S. This study investigates whether the VFD rule changes affected the occurrence of tetracycline-resistant and erythromycin-resistant bacteria (Salmonella, Escherichia, and Campylobacter) in retail meats in the U.S. Methods Multivariable mixed effect logistic regression models were used to analyze 2002-2019 retail meats surveillance data from the National Antimicrobial Resistance Monitoring System (NARMS) in the U.S. Variables included VFD rule changes, meat type, quarter of year, and raising claims. A potential association between these variables and the occurrence of tetracycline-resistant and erythromycin-resistant bacteria (Salmonella, Escherichia, and Campylobacter) in retail meats was estimated. Results Analysis included data regarding tetracycline-resistant Salmonella (n = 8,501), Escherichia (n = 20, 283), Campylobacter (n = 9,682), and erythromycin-resistant Campylobacter (n = 10,446) in retail meats. The odds of detecting tetracycline-resistant Escherichia (OR = 0.60), Campylobacter (OR = 0.89), and erythromycin-resistant Campylobacter (OR = 0.43) in chicken breast significantly decreased after the VFD rule changes, compared to the pre-VFD rule change period. The odds of detecting tetracycline-resistant Salmonella (0.66), Escherichia (OR = 0.56), and Campylobacter (OR = 0.33) in ground turkey also significantly decreased. However, the odds of detecting tetracycline-resistant Salmonella (OR = 1.49) in chicken breast and erythromycin-resistant Campylobacter (OR = 4.63) in ground turkey significantly increased. There was no significant change in the odds of detecting tetracycline-resistant Salmonella and Escherichia in ground beef or pork chops. Conclusions The implementation of VFD rule changes had a beneficial effect by reducing the occurrence of tetracycline-resistant and erythromycin-resistant bacteria in chicken and ground turkey. Ongoing surveillance of antimicrobial resistance and antimicrobial use could complement the implementation of stewardship such as VFD rule in food-producing animals in the U.S.